Landau-Zener transitions in a semiconductor quantum dot - Murgida, Gustavo Ezequiel (2009)
We study the transitions between neighboring energy levels in a quasi-one-dimensional semiconductor quantum dot with two interacting electrons in it, when it is subject to a linearly time-dependent electric field. We analyze the applicability of a simple two-level Landau-Zener model to describe the evolution of the probability amplitudes in this realistic system. We show that the Landau-Zener model works very well when it is viewed in the adiabatic basis, but it is not as robust in the diabatic basis.